A Pilot Study of a Comparison of Glycemic Control in Critically Ill Patients - Rungsun Bhurayanontachai; Piyada Kongkamol; Chanon Kongkamol (Journal of Health Science and Medical Research (JHSMR), 2010)
Objective: To compare glycemic control in the critically ill patients between a single dose of subcutaneous injection of insulin glargine and a continuous intravenous infusion of regular insulin. Study design: Prospective, experimental pilot study. Subjects: Twelve critically ill patients with hyperglycemia who required glycemic control according to the standard continuous intravenous infusion of regular insulin protocol with constant insulin infusion rate per hour for at least 24 hours. Materials and Methods: These patients received a single dose subcutaneous injection of insulin glargine, which was equal to 80% of the total daily requirement of regular insulin in the previous 24 hours. The blood sugar level was continuously checked every 2 hours for the next 24 hours after either insulin glargine administration or the blood sugar level was outside the desired range, in which case the standard regular insulin infusion was then resumed. The blood sugar levels before and after injection of insulin glargine was then compared by pair t-test and generalized linear mixed models (GLMM). Results: Of the 12 patients, only 8 patients achieved a good glycemic control with the single dose subcutaneous injection of insulin glargine. However, the mean blood sugar after injection of insulin glargine was statistically significantly higher than the continuous intravenous infusion of regular insulin period (175.62±58.82 mg/dl vs. 145.45±30.33 mg/dl, p<0.001) without random effects. Conclusion: The single dose of a subcutaneous injection of insulin glargine, with the dose of 80% of total daily requirement dose of regular insulin, was inadequate for glycemic control when compare to the standard continuous intravenous infusion of regular insulin.